Understanding the topologies of innovation networks in knowledge-intensive sectors - Salavisa, I.; Salavisa, I.; Sousa, C.; Fontes, M. (DINÂMIA'CET-IUL Working Paper n.º 2011/09, 2011)
The main goal of this paper is to compare the networks mobilised by young entrepreneurial firms from two knowledge intensive sectors – molecular biotechnology and software for telecommunications – to access resources required for innovation. Such a comparison allows similarities and differences between networks to be identified and explained. The analysis focuses on formal and informal networks and on the relevant types of resources. It applies a methodology that draws on a vast array of data to capture the nature and content of a broad range of relationships developed by the firms in their innovative process. The results show that networks are quite contrasted in and across the two sectors, due both to the specificity of the resources searched for and the mode of organisation of the sectors. Furthermore, the results shed light on the specificities of formal versus informal networks. Finally, they provide novel insights into the organisation and dynamics of the sectors, taking into account both the characteristics and strategies of the firms and the specificity of the environment in the Portuguese case. The approach provides tools to study the innovative process in knowledge intensive sectors which may be applied to different national and sectoral contexts.